Steady survival improvements in soft tissue and bone sarcoma in the Nordic countries through 50 years - Tichanek, Filip; Försti, Asta; Hemminki, Otto; Hemminki, Akseli; Hemminki, Kari (Cancer epidemiology, 2024)
PURPOSE: Sarcomas are rare cancers with many subtypes in soft tissues, bone and cartilage. International survival trends in these cancers are not well known. We present 50-year survival trends for soft tissue sarcoma (STS) and bone sarcoma (BS) in Denmark (DK), Finland (FI), Norway (NO) and Sweden (SE). METHODS: Relative 1-, 5/1 conditional- and 5-year survival data were obtained from the NORDCAN database for years 1971-20. We additionally estimated annual changes in survival rates and determined significant break points. RESULTS: In the last period, 2016-20, 5-year survival in STS was best for NO men (74.6%) and FI women (71.1%). For the rarer BS, survival rates for SE men (72.0%) and DK women (71.1%) were best. Survival in BS was lower than that in STS in 1971-75 and the difference remained in 2016-20 for men, but for women the rates were almost equal. Sex- and country-specific differences in survival in STS were small. The 50-year improvement in 5-year survival in STS was highest in NO men, 34.0 % units and FI women, 30.0 % units. The highest improvements in BS were in SE men 26.2 % units and in FI women 29.2 % units. CONCLUSIONS: The steady development in survival over the half century suggests contribution by stepwise improvements in diagnostics, treatment and care. The 10-15% mortality in the first year probably indicates diagnostic delays which could be improved by organizing patient pathways for aggressive rare diseases. Early diagnosis would also reduce metastatic disease and breakthroughs in treatment are a current challenge.
Keywords: Registries; Soft Tissue Neoplasms; osteosarkom; Humans; nádory kostí; lidé středního věku; sarkom; Finland; registrace; Female; Bone Neoplasms; mladý dospělý; dospělí; Aged; Osteosarcoma; senioři; lidé; Relative survival; nádory měkkých tkání; Skandinávie a severské státy; Adult; Diagnostics; Finsko; ženské pohlaví; Sarcoma; Male; Middle Aged; Adolescent; Incidence; Young Adult; míra přežití; mužské pohlaví; Scandinavian and Nordic Countries; Treatment; mladiství; Conditional survival; Survival Rate